2004
DOI: 10.1128/aac.48.7.2370-2378.2004
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial Quinolines and Artemisinin Inhibit Endocytosis in Plasmodium falciparum

Abstract: Endocytosis is a fundamental process of eukaryotic cells and fulfills numerous functions, most notably, that of macromolecular nutrient uptake. Malaria parasites invade red blood cells and during their intracellular development endocytose large amounts of host cytoplasm for digestion in a specialized lysosomal compartment, the food vacuole. In the present study we have examined the effects of artemisinin and the quinoline drugs chloroquine and mefloquine on endocytosis in Plasmodium falciparum. By using novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
69
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(81 citation statements)
references
References 53 publications
10
69
0
2
Order By: Relevance
“…This finding is in agreement with previous work showing that artemisinin treatment leads to an accumulation of undigested hemoglobin in the parasite (22). We also showed that hemoglobin uptake and subsequent hydrolysis are required for potent artemisinin activity.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This finding is in agreement with previous work showing that artemisinin treatment leads to an accumulation of undigested hemoglobin in the parasite (22). We also showed that hemoglobin uptake and subsequent hydrolysis are required for potent artemisinin activity.…”
Section: Discussionsupporting
confidence: 83%
“…P. falciparum takes up and degrades host hemoglobin in an acidic digestive vacuole in a process that begins in the mid ring stage and reaches a peak in the mid trophozoite stage (20,21). Some antimalarials, including artemisinin, are reported to inhibit hemoglobin uptake (22), but it is not clear if this is a direct effect, or a consequence of parasite killing. To monitor hemoglobin uptake and parasite viability simultaneously we established a correlative flow cytometric assay employing parasites that had invaded resealed RBCs containing a fluorescent marker (21).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the similarities between the current model for hemoglobin transport and the endocytic pathway in higher eukaryotes (Goldberg et al, 1990;Hoppe et al, 2004;Langreth et al, 1978;Saliba et al, 2003), we investigated the role of actin dynamics in hemoglobin transport to the FV. Actin has been shown to play various regulatory roles in endocytosis, including recruiting endocytic components to the plasma membrane, initiating plasma membrane invaginations, vesicle scission and transport to endocytic compartments (Kaksonen et al, 2006;Qualmann et al, 2000;Smythe and Ayscough, 2006).…”
mentioning
confidence: 99%
“…Arylaminoalcohols (Fig. 4) seem to interfere with the heme digestion [35,36]. Amplification of the pfmdr1 gene appears to be the main factor in arylaminoalcohol resistance [37 -42].…”
Section: Arylaminoalcoholsmentioning
confidence: 99%